2009
DOI: 10.1111/j.1468-0297.2009.02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Choice under Uncertainty: Evidence from Ethiopia, India and Uganda

Abstract: We review experimental evidence collected from risky choice experiments using poor subjects in Ethiopia, India and Uganda. Using these data we estimate that just over 50% of our sample behaves in accordance with expected utility theory and that the rest subjectively weight probability according to prospect theory. Our results show that inferences about risk aversion are robust to whichever model we adopt when we estimate each model separately. However, when we allow both models to explain portions of the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 197 publications
(143 citation statements)
references
References 58 publications
8
130
3
2
Order By: Relevance
“…There has been much interest in cross country differences in attitudes towards uncertainty, and numerous studies have measured attitudes toward prospects with objectively known payoff distributions in developing countries and small scale societies (Binswanger 1980;Bohnet et al 2008;Kuznar 2001;Yesuf and Bluffstone 2009;Harrison et al 2010;Dillon and Scandizzo 1978;Elamin and Rogers 1992). Most of these studies found a similar degree of risk aversion as in typical student samples from developed countries.…”
Section: Discussionmentioning
confidence: 64%
“…There has been much interest in cross country differences in attitudes towards uncertainty, and numerous studies have measured attitudes toward prospects with objectively known payoff distributions in developing countries and small scale societies (Binswanger 1980;Bohnet et al 2008;Kuznar 2001;Yesuf and Bluffstone 2009;Harrison et al 2010;Dillon and Scandizzo 1978;Elamin and Rogers 1992). Most of these studies found a similar degree of risk aversion as in typical student samples from developed countries.…”
Section: Discussionmentioning
confidence: 64%
“…Future research should not neglect the burgeoning field of behavioral economics, which assesses the likelihood of significant differences across men and women in procrastination and time preference, attitudes to risk and aversion to loss (28), willingness to invest in competitive social situations (29), and preferences to structure social arrangements in ways that are perceived to be fair. Moreover, it has also become clear that financial arrangements of many African households are heavily influenced by considerations of bargaining within households and the difficulty of commitment to respect individual control over income.…”
Section: Gendered Choice In Householdsmentioning
confidence: 99%
“…Our study is part of a growing emphasis on laboratory experiments in field settings that focus on low-income populations, primarily in developing countries (e.g., Ashraf 2009, Binswanger 1980, de Oliveira et al 2011, Harrison et al 2009, Karlan 2005, Meier and Sprenger 2010, Tanaka et al 2010. See also Banerjee andDuflo 2008, andCardenas andCarpenter 2008 for overviews).…”
Section: Introductionmentioning
confidence: 99%
“…Note that our purpose is not program evaluation; in particular, we do not attempt to discover the return to additional human capital investment or to assess whether a policy to subsidize human capital acquisition by the poor would be cost-effective. Instead we collect information that could be used to improve the design of such a policy by eliciting preferences for education using actual choices between cash and funds designated for education expenses, and assessing the response of the investment decisions of the poor population to various subsidy levels.Our study is part of a growing emphasis on laboratory experiments in field settings that focus on low-income populations, primarily in developing countries (e.g., Ashraf 2009, Binswanger 1980, de Oliveira et al 2011, Harrison et al 2009, Karlan 2005, Meier and Sprenger 2010, Tanaka et al 2010. See also Banerjee andDuflo 2008, andCardenas andCarpenter 2008 for overviews).…”
mentioning
confidence: 99%